Uwagi o teście zgodności Li wykorzystującym metodę jądrową - Baszczyńska, Aleksandra (A Note on the Li Goodness of Fit Test Using Kernel Method, 2007)
Kernel method is used, first of all, in nonparametric estimation of density function. There are statistical tests where nonparametric kernel estimator of density function is applied in construction of test's statistic. They are, among others, goodness of fit tests (including normality tests), independence tests and symmetry ones. In the paper, construction and properties' examination of goodness of fit test, proposed by Li, are presented. On the basis of simulation study the trial of choosing the best test's statistic of Li test is made. The analysis of influence of kernel method's parameter (kernel function) on the result of test's procedure is also regarded. Li test and some others nonparametric goodness of fit tests are used in examination of consistence of distributions of index of perception corruption in two years: 1996 and 2005.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 31-40